Stimulated Transitions of Directed Nonequilibrium Self‐Assemblies. Issue 43 (10th October 2017) - Steinschulte, Alexander A.; Scotti, Andrea; Rahimi, Khosrow; Nevskyi, Oleksii; Oppermann, Alex; Schneider, Sabine; Bochenek, Steffen; Schulte, Marie F.; Geisel, Karen; Jansen, Felicitas; Jung, Andre; Mallmann, Sabrina; et al.
Abstract: Near‐equilibrium stimulus‐responsive polymers have been used extensively to introduce morphological variations in dependence of adaptable conditions. Far‐less‐well studied are triggered transformations at constant conditions. These require the involvement of metastable states, which are either able to approach the equilibrium state after deviation from metastability or can be frozen on returning from nonequilibrium to equilibrium. Such functional nonequilibrium macromolecular systems hold great promise for on‐demand transformations, which result in substantial changes in their material properties, as seen for triggered gelations. Herein, a diblock copolymer system consisting of a hydrophilic block and a block that is responsive to both pressure and temperature, is introduced. This species demonstrates various micellar transformations upon leaving equilibrium/nonequilibrium states, which are triggered by a temperature deflection or a temporary application of hydrostatic pressure. Abstract : Temporary pressure or temperature deflections induce property and morphology changes of easily prepared and kinetically stable nonequilibrium micelles. These systems allow a stimulated physical gelation at constant conditions before and after trigger application. As an extraordinary example, a specific polymer, which can show all principle micellar morphologies at the same concentration c, pressure p, and temperature T, is highlighted.